Visualisasi Kinerja Keuangan Properti di Indonesia - Ramadhanti, Andita; Yuniar, Iga Amalia (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2023)
Property companies’ financial performance faces collapse threat post pandemic COVID-19. This study aims to analyze the financial performance of property companies in 2019-2021 and design a visualization of it to support investment decision-making. This study uses secondary data from financial reports. Research’s objects are property company that is in BEI’s main board, specifically PT. Ciputra Development Tbk. (CTRA), PT. Pakuwon Jati Tbk. (PWON), and Alam Sutera Realty Tbk. (ASRI). The result of the study shows that property companies have the highest solvability other than the other ratios. Based on the visualization from the radar chart, PWON is the first company to prioritize investment.